2019
DOI: 10.5217/ir.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of colorectal cancer in Asia

Abstract: habits, physical activity, smoking and alcohol consumption. About 25% of the CRC cases have a genetic predisposition, and 5% of CRC patients have inherited factors associated with its development. 5,6 Family history of CRC and the presence of common chronic conditions, such as metabolic syndrome and fatty liver, were among the key factors reported by existing literature. In a report from Continuous Update Project, 7 being physically active, consuming wholegrains, dairy products, foods containing dietary fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
167
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(174 citation statements)
references
References 106 publications
(131 reference statements)
2
167
1
4
Order By: Relevance
“…There are some studies [39][40][41] that consider height in the analysis as risk factors for colorectal cancer, and the results of the analysis are also reported to be significant. Based on these similar previous studies, this study considered the relationship between height and colorectal cancer but found no significant correlation.…”
Section: Discussionmentioning
confidence: 96%
“…There are some studies [39][40][41] that consider height in the analysis as risk factors for colorectal cancer, and the results of the analysis are also reported to be significant. Based on these similar previous studies, this study considered the relationship between height and colorectal cancer but found no significant correlation.…”
Section: Discussionmentioning
confidence: 96%
“…Colorectal cancer (CRC) is the third most common cancer worldwide, comprising a considerable portion of the disease burden. About half of new cases and deaths occur in Asia, 1 where awareness of CRC has risen in recent times. Approximately 20% of new cases present with distant metastases 2 and 20%-25% of localised cases eventually experience recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of colorectal cancer has been increasing worldwide. 1 Most colorectal cancers originate from precancerous polyps. 2 Therefore, to decrease mortality, it is extremely important to identify precancerous polyps or early colorectal www.irjournal.org cinoma and lymphovascular invasion or tumor budding.…”
Section: Introductionmentioning
confidence: 99%